2015
DOI: 10.5539/jas.v8n1p92
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Loan Repayment among Small Holder Cooperative Farmers in Remo Division, Ogun State, Nigeria

Abstract: This study investigated the factors that are crucial in improving small holder cooperative farmers' loan repayment in Remo Division of Ogun state, Nigeria. Primary data used for the study were collected with the aid of well-structured questionnaire. Multi-stage sampling techniques were used to select the 120 respondents. The data were analyzed using descriptive statistics and probit regression model. The results of the descriptive analysis showed that about 56% of the respondents were able to repay their loans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
3
0
0
Order By: Relevance
“…Results on family size revealed that majority (48.8%) had a large family size of 4-7 persons. This conforms with the findings of Isito et al [28] who reported an average of 6 members per family. Having a larger family especially those with higher number of adult children would enable small-scale cassava-based farmers to have enough labour to work in the farm.…”
Section: Socio-economic Characteristics Of Farmerssupporting
confidence: 93%
See 2 more Smart Citations
“…Results on family size revealed that majority (48.8%) had a large family size of 4-7 persons. This conforms with the findings of Isito et al [28] who reported an average of 6 members per family. Having a larger family especially those with higher number of adult children would enable small-scale cassava-based farmers to have enough labour to work in the farm.…”
Section: Socio-economic Characteristics Of Farmerssupporting
confidence: 93%
“…Majority of the farmers were in the range of 41-50 years (37.5%) indicating that the farmers were young, energetic, still active in farming and dynamic. This is in line with the findings of Isito, Otunaiya, Adeyonu and Fabiyi [28] who reported an average of 47 years for small holder farmers. This result is slightly higher than those of Abula, Otitolaiye, Ibitoye and Orebiyi [29] who reported a mean age of 44 years for farmers in their findings.…”
Section: Socio-economic Characteristics Of Farmerssupporting
confidence: 92%
See 1 more Smart Citation